Interconnection of a Wind Driven DC Machine with the Power Utilities Grid - Taleb, Maamar (Journal of Technology Innovations in Renewable Energy, 2013)
A wind driven DC machine is interconnected with the power utilities grid. The wind driven DC machine is operated in the regenerative mode and that is to guaranty the extraction of the real power from the wind driven generator and inject it into the power grid. This is done through the use of a single phase full wave controlled converter operating in “ an inverter mode of operation”. At any pretended surrounding weather conditions, maximum extraction of power from the renewable energy source (ie. Wind energy source) is targeted. This is done through the realization of a self-adjusted firing angle controller responsible of triggering the semiconductor elements of the controlled converter. An active power filter is shunted with the proposed setup to guaranty the sinusoid quality of the power utilities line current. The overall performance of the proposed system has been simulated in MATLAB/SIMULINK environment. Quite satisfactory and encouraging results have been obtained.